2020
DOI: 10.4236/jep.2020.114020
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and External Costs of Yali Hydropower Plant and Policy Recommendations in Vietnam

Abstract: The purpose of this study is to estimate the monetary value of the main environmental and external costs of Yali Hydropower Plant (YHPP) and to incorporate them into the financial viability indices of the plant, namely its net present value and electricity price. The results were found that if the electricity price is kept at its original level of 5.2 US cents/kWh to cover direct costs only, the net present value of the plant would be reduced to about 27% by incorporating environmental and external costs. Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Singh [25] examined the cereal crops, sugarcane, and cotton contribution in the production of surplus biomass. In the study by Song et al [26] on hydro power plants, they concluded that the electricity price would have to be increased to 5.7 US cents/kWh in order to cover the full costs of the Yali hydro power plant. In the environmental analysis of Roy et al [27], they found an environmental benefit value of about 430,014 USD/year of using biomass power plants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Singh [25] examined the cereal crops, sugarcane, and cotton contribution in the production of surplus biomass. In the study by Song et al [26] on hydro power plants, they concluded that the electricity price would have to be increased to 5.7 US cents/kWh in order to cover the full costs of the Yali hydro power plant. In the environmental analysis of Roy et al [27], they found an environmental benefit value of about 430,014 USD/year of using biomass power plants.…”
Section: Literature Reviewmentioning
confidence: 99%